An evaluation of counselling approach on communication apprehension among students in higher education - Majid, Nor Hernamawarni Abd; Ahmad, Nor Shafrin; Aman, Rahimi Che; Yaacob, Nik Rosila Nik; Ali, Nur Hikmah Mubarak (Institute of Advanced Engineering and Science, 2025)
Communication apprehension is a major challenge in higher education, affecting students’ communication ability, which is crucial for academic success and future employability. It manifests as public speaking anxiety, reluctance in group discussions, and avoidance of classroom interactions, hindering soft skill development and academic performance. This study aims to evaluate the effectiveness of counselling approaches in reducing communication apprehension among students in higher education. Consequently, counselling intervention modules, including the solution-focused brief cognitive behavior (SFBCB) therapy and group counselling (GC) modules, were developed. Sixty students who participated in this study were studying at a public university. Pre-tests, post-tests, and follow-up tests were administered using the personal reports of communication apprehension questionnaire to measure changes in apprehension levels across different communication contexts, including group discussions, meetings, dyadic interactions, and public speaking. The results demonstrated that both intervention modules significantly reduced communication apprehension, with improvements in participants’ confidence and communication abilities. In conclusion, the study highlights the effectiveness of integrating solution-focused and cognitive-behavioral techniques in counselling interventions to mitigate communication apprehension. These findings suggest that such approaches can be valuable tools in higher education to enhance students’ communication skills, ultimately contributing to their academic success and personal growth.